Indonesian EFL Novice Teachers' Strategies in Conquering Online Learning Challenges - Utin Novianti Alawiyah; Joko Nurkamto; Nur Arifah Drajati (AL-ISHLAH: Jurnal Pendidikan, 2023)
The researchers purposely conducted this qualitative study to determine the teaching strategies used by Indonesian EFL novice teachers in dealing with the online learning challenges they have adapted to during COVID-19 and how their strategy fulfilled the need for online learning. Using interviews and document analysis, the researchers presented strategies of five novice EFL teachers practised in Indonesia to adjust to the online learning challenges toward their teaching they experienced during the COVID-19 pandemic. The data analysis is done by transcribing, analyzing, coding, describing, and concluding from teachers' guided written reflections and semi-structured interviews. The results were also analyzed under the conceptual model of five types of interactions by Wang et al. The findings revealed that the teachers employed several strategies to minimize technical problems, create efficient learning resources, and adapt to an ERT-based learning environment. Despite these beneficial strategies, they cannot fulfil the successful criteria of online learning. Therefore, there is a need for improvement. This study is limited to a small number of participants, which may need to adequately expose all of the strategies employed by other novice teachers during online classes. Additionally, this study did not further investigate learning achievement, which needs to be investigated for future research.